2015
DOI: 10.1111/jph.12363
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Syzygium aromaticum and Zanthoxylum xanthoxyloides Essential Oils Against Phytophthora megakarya

Abstract: The aim of this study was to assess the chemical composition and the antimicrobial activity of essential oils of dried fruits and buds of Zanthoxylum xanthoxyloides (Z. xanthoxyloides) and Syzygium aromaticum (S. aromaticum or clove), respectively, against Phytophthora megakarya (P. megakarya). Essential oils were extracted by hydrodistillation, and their composition was determined by gas chromatography and by gas chromatography coupled with Mass Spectrometry. The minimal inhibitory concentration (MIC) and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Moreover, Nana et al. () also showed the in vivo effectiveness of clove oil to protect cocoa pod against black pod disease. In addition, the lipophilic property of the essential oil that readily diffuses into plant tissues across membranes and acts on mycelia and conidia could justify the reduction of the necrosis rate (Xing et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nana et al. () also showed the in vivo effectiveness of clove oil to protect cocoa pod against black pod disease. In addition, the lipophilic property of the essential oil that readily diffuses into plant tissues across membranes and acts on mycelia and conidia could justify the reduction of the necrosis rate (Xing et al.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils extracted from clove have been previously investigated for chemical composition and biological activities. Nana et al (2015) steamed distillated clove oil from another locality of Cameroon and obtained a yield of 10.54%. In this study, we obtained a significantly lower yield (6.34%), supporting the fact that the rate of secretion of secondary metabolites by plants can vary depending on the site.…”
Section: Discussionmentioning
confidence: 99%
“…By the last technology, many spots were observed and the spots were scratched and the chemical components were extracted by ethanol. Finally, it was gained the alcoholic extraction of clove that used in further experiments (9). Several previous studies focused on the extraction of different compounds from clove (Syzygium aromaticum) flowers and used in different fields of medicine.…”
Section: Extraction Separation and Purification Of Chemical Compoundmentioning
confidence: 99%
“…Both of isolates were cultured into Muller Hinton broth prior to experiment (9). The disc diffusion method was used to assessment the antibacterial activity of the extract against Bacillus and Serratia marcescens.…”
Section: Antibacterial Activity Of Supernatant Of Extractmentioning
confidence: 99%
“…Also, Zanthoxylum species have a folklore history in the treatment of various diseases, such as inflammation [15], toothache, lumbago [16], ascarid infection [17], sickle-cell anaemia, and malaria. Literatures have also shown that Zanthoxylum species possess a potential antiinsect [7,18,19], antimicrobial [20], antibacterial [21], and antifungal [22] activities.…”
Section: Introductionmentioning
confidence: 99%